(untitled) (Raparin Journal of Humanities (RJH), 2024)
The aim of the study is to determine the effectiveness of the proposed e-learning program according to the academic boredom of self-learning. The experimental approach was used for two independent, equal groups, (44) male and female students were deliberately chosen. The research tool consisted of 45 items. Honesty and constancy were acceptable. The results showed that there were statistically significant differences between the academic post boredom test in favor of the experimental group. The differences were statistically significant in the pre and post tests of the experimental group, and the result was in favor of the post test. There were no statistically significant differences in academic boredom between the pre and post test of the female group in the experimental group. No statistically significant differences were found for females of academic boredom between the pre and post test for both groups. There were statistically significant differences among males from academic boredom between the pre and post tests for both groups in favor of the experimental groups. The research presented some recommendations and suggestions.